A novel formulation of 3D Jeffery fluid flow near an irregular permeable surface having chemical reactive species. (May 2021) - Khan, Mumtaz; Rasheed, Amer; Ali, Shafqat; Azim, Qurat-ul-Ain
The main objective of this paper is to offer a comprehensive study regarding solar radiation and MHD effects on 3D boundary layer Jeffery fluid flow over a non-uniform stretched sheet along with variable thickness, porous medium and chemical reaction of first order are assumed. The system of equations representing temperature, velocity and concentration fields are converted into dimensionless form by introducing dimensionless variables. Thereafter, the aforesaid equations are solved with the help of BVP4C in MATLAB. The numerical results obtained through this scheme are more accurate when compared with those in the existing literature. In order to have a pictorial representation, the effects of material and flow parameters on velocity, temperature and concentration profiles are presented through graphs. Moreover, the numerical values of heat and mass transfer rate and skin friction coefficient are given in tabular form. It is evident from the acquired results, that the velocity offers two fold behavior for variable thickness parameter that is, n <  1 close and away from the non-uniform surface. It is also noted that the axial and transverse velocities show an increasing behavior for Deborah number while the fluid temperature and concentration shows opposite behavior at the same time.